Typification and nomenclature of the names published in Plantae Serbicae Rariores aut Novae—Decas III - Clementi, Moreno; Vukojičić, Snežana; Miola, Antonella; Niketić, Marjan (Phytotaxa, 2016)
We provide information on the typification of the names of one genus (Lactucopsis), two sections (L. sect. Mulgediopsis, L. sect. Prenanthopsis), two unranked subgeneric names (Hieracium [unranked] Chlorocarpa, H. [unranked] Melanocarpa), ten species (Dianthus moesiacus, Eryngium palmatum, Haplophyllum boissierianum, Hieracium schultzianum, Lactucopsis aurea, Lactucopsis brevirostris, Lactucopsis mulgedioides, Mulgedium sonchifolium, Picridium macrophyllum, Stachys anisochila), and one form (Gypsophila spergulifolia f. serbica) validly published in Roberto de Visiani and Josif Pančić’s work Plantae Serbicae Rariores aut Novae—Decas III, published in 1870, and one variety (Knautia macedonica var. lyrophylla) published in Verzeichnis der in Serbien wildwachsenden Phanerogamen (1856). Additional nomenclatural notes deal with three other species, five new combinations, seven invalid names and one invalid combination that were also discussed or published in Visiani & Pančić (1870). Seven nomenclatural types for eight validly published taxa are designated here.